Stress Response and Perinatal Reprogramming: Unraveling (Mal)adaptive Strategies - Laura Musazzi; Jordan Marrocco (Neural Plasticity)
Environmental stressors induce coping strategies in the majority of individuals. The stress response, involving the activation of the hypothalamic-pituitary-adrenocortical axis and the consequent release of corticosteroid hormones, is indeed aimed at promoting metabolic, functional, and behavioral adaptations. However, behavioral stress is also associated with fast and long-lasting neurochemical, structural, and behavioral changes, leading to long-term remodeling of glutamate transmission, and increased susceptibility to neuropsychiatric disorders. Of note, early-life events, both in utero and during the early postnatal life, trigger reprogramming of the stress response, which is often associated with loss of stress resilience and ensuing neurobehavioral (mal)adaptations. Indeed, adverse experiences in early life are known to induce long-term stress-related neuropsychiatric disorders in vulnerable individuals. Here, we discuss recent findings about stress remodeling of excitatory neurotransmission and brain morphology in animal models of behavioral stress. These changes are likely driven by epigenetic factors that lie at the core of the stress-response reprogramming in individuals with a history of perinatal stress. We propose that reprogramming mechanisms may underlie the reorganization of excitatory neurotransmission in the short- and long-term response to stressful stimuli.